Comparative Study on the Effect of Rosemary Extract and Sodium Ascorbate on Lipid and Pigment Oxidative Stability of Liver Pate - Haile, Demewez Moges; Smet, Stefan De; Clays, Erik; Vosen, Els (Journal of Meat Science, 2012)
A comparative study on the antioxidant effect of rosemary extract (RE) and sodium ascorbate (SA) on lipid and color oxidation of liver pâté was done. During the 48 hour experimental time all the pâtés were wrapped in a foil and stored in cold room of 3.5°C under light of 1000 lux. Color stability was monitored by instrumental color measurement (CIE L*a*b* color space) lipid stability was measured by the determination of the 2-thiobarbituric acid reactive substances (TBARS). In the present study RE doses range (0,125, 250, 375 and 500 ppm) showed no significant (p>0.05) and linear effect on color stability. However the RE revealed a significant effect (p0.05) effect against lipid and color oxidation.
Keywords: liver pâté; Color and lipid oxidation; TBARS; CIE L*a*b*; Rosemary extract; Sodium ascorbate